The Role of the Molecular Subtypes in the Prognosis of Breast Cancer Patients - Nikolov, Stoyan; Enchev, Emil; Minkov, Georgi; Dimitrov, Evgeni; Ivanova, Koni; Gulubova, Maya; Vlaykova, Tatyana; Yovtchev, Yovcho (Open Access Macedonian Journal of Medical Sciences, 2020)
BACKGROUND: Understanding the biology of the tumor, by dividing it into molecular subtypes, has made it possible to individualize the therapeutic approach in high-risk patients. AIM: We aimed to determine the importance of established molecular subtypes in the prognosis and the importance of disease-free and overall survival (OS) in patients with non-metastatic breast cancer. MATERIALS AND METHODS: We analyzed 94 patients with non-metastatic breast cancer for the period 2010–2018. The median follow-up time was 60 months. The mean age in the study group was 60.03 years (SD ± 10.52). According to the characteristics of the studied indicators, we divided the group into Luminal A (n-59 [62.7%]), Luminal B/HER2 (−) (n-2 [2.1%]), Luminal B/HER2 (+) (n-8 [8.5%]), HER2 overexpressing (n-3 [3.2%]), and triple-negative subtype (n-22 [23.5%]). In all patients in the study group, we analyzed the 5-year overall survival (OS) and disease-free survival (DFS) and referred it to molecular subtypes, lymphatic status, HER-2 status, the presence or absence of endocrine therapy for the follow-up period, tumor differentiation, and type of surgery. RESULTS: We observed the 5-year OS in 92% of patients identified as Luminal A; at 50% of Luminal B/HER2 (−) neg.; in 62.5% with Luminal B/HER2 (+), in 67% with HER2-overexpressing carcinoma; and in 66.7% of patients with triple-negative subtype. The total cancer-associated mortality rate in the analyzed period reached 15.9% (n = 15). Patients with mastectomy (p = 0.019, p = 0.027), positive axilla with more than 4 lymph node (LN) (p = 0.000; p = 0.000), and Luminal B/HER-2 (+) tumors (p = 0.004; p = 0.003) were the independent prognostic factors for worse DFS and OS in our study group. Histological differentiation and HER-2 expression were in unsatisfactory correlation (p = 0.077; p = 0.044 and p = 0.081; p = 0.055, respectively). CONCLUSION: Molecular subtypes are essential in the prognosis of breast cancer and maybe a criterion for an individualized therapeutic approach.